Region Charkov, Ukraine: Die Infrastruktur im Gebiet der Dnepr-Severkij Donec-Wasserscheide in spätrömischer Zeit und zu Beginn der Völkerwanderungszeit - Schultze, Erdmute (e-Forschungsberichte des DAI, 2023)
Research in the area of the modern district of Kharkiv (East Ukraine) is devoted to the settlement history of the 4th and 5th century AD, especially of the Chernyakhov culture. The investigations included excavations in Voitenki, a well known archaeological complex of the Chernyakhov culture consisting of a settlement and a cemetery. Surveys conducted along the rivers Kolomak, Mzha and in the area of Zmiev provided material and GPS-data of other mostly unknown archaelogical sites. Two test drillings were made for collecting data for a palynological analysis.